2021
DOI: 10.1007/s12672-021-00434-5
|View full text |Cite|
|
Sign up to set email alerts
|

Identification hub genes of consensus molecular subtype correlation with immune infiltration and predict prognosis in gastric cancer

Abstract: Gastric cancer (GC) has a great fatality rate, meanwhile, there is still a lack of available biomarkers for prognosis. The goal of the research was to discover key and novel potential biomarkers for GC. We screened for the expression of significantly altered genes based on survival rates from two consensus molecular subtypes (CMS) of GC. Subsequently, functional enrichment analysis showed these genes involved in many cancers. And we picked 6 hub genes that could both secreted in the tumor microenvironment and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In head and neck squamous cell carcinoma, the molecular features of different subtypes were evaluated for potentially effective therapeutic agents ( Zhang et al, 2021 ). In gastric cancer, consensus molecular subtypes were associated with immune infiltration for prediction of survival ( Yu et al, 2021a ). In metastatic colorectal cancer, consensus molecular analysis demonstrated that the consensus molecular subtype 2 was the predominant subtype in left-sided and associated with the best outcome from the addition of bevacizumab to first-line chemotherapy ( Mooi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck squamous cell carcinoma, the molecular features of different subtypes were evaluated for potentially effective therapeutic agents ( Zhang et al, 2021 ). In gastric cancer, consensus molecular subtypes were associated with immune infiltration for prediction of survival ( Yu et al, 2021a ). In metastatic colorectal cancer, consensus molecular analysis demonstrated that the consensus molecular subtype 2 was the predominant subtype in left-sided and associated with the best outcome from the addition of bevacizumab to first-line chemotherapy ( Mooi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of molecular subtypes in cancers contributes to more accurate prognostic assessment due to substantial phenotypic and molecular heterogeneity among patients, and simultaneously is an important basis for individualized therapy and precision medicine. Studies about molecular subtypes have been widely concerned with diverse cancer types, such as breast cancer [ 31 , 32 ], colon cancer [ 33 , 34 ] and gastric cancer [ 35 ], which provide potentially crucial data for diagnosis and treatment. In prostate cancer, via a comprehensive molecular analysis, seven major molecular subtypes are characterized by the Cancer Genome Atlas Research Network, TCGA-PRAD project [ 36 ], and relevant studies are also carried out to provide more data in cancer treatment [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, OGN was discovered to be upregulated in dormant breast cancer cells compared to proliferative cells, serving as a marker for breast cancer and a prognostic factor for breast cancer patients [ 94 ]. OGN was also found to be significantly associated with poor survival in patients with gastric cancer (GC), and its expression increased as the cancer progressed, according to a functional enrichment analysis [ 95 ]. According to a bioinformatic analysis, OGN plays vital roles in immune surveillance and tumor progression in papillary thyroid cancer [ 96 ].…”
Section: Ogn Function In Tumorigenesismentioning
confidence: 99%